Green, practical & scalable approach towards the synthesis of valuable α-keto amides using a metal-free catalyst under solvent-free conditions - Bankar, Shubham R.; Ghadge, Sambhaji S.; Jadhav, Vrushali H. (New Journal of Chemistry, 2023)
alpha-Ketoamides are very important motifs as they are present in many natural products, drugs & biologically important molecules. We synthesized a very simple, cheap, eco-friendly & reusable glucose-based carbonaceous material (GCM), which showed high performance as a catalyst in the oxidative cross-dehydrogenative coupling (CDC) reaction of alpha-ketoaldehydes with amines for the synthesis of alpha-ketoamides. The GCM catalyst was also very efficient for one-pot two-step synthesis of alpha-ketoamides from alpha-ketoalcohols as well. The GCM catalyst was able to catalyze alcohol oxidation in alpha-ketoalcohols followed by CDC reaction with amines to form alpha-ketoalcohols. The reactions were found to proceed smoothly at a low temperature of 50 degrees C using a green & economical metal-free catalyst under base-free, ligand-free & solvent-free reaction conditions to get the corresponding alpha-ketoamides in good to excellent yields. The results demonstrated that the GCM catalyst showed acidic as well as superior oxidising catalytic activity due to the presence of a carboxylic acid (-COOH) and hydroxyl (-OH)-enriched carbonaceous framework, which enabled the synthesis of important alpha-ketoamide motifs. The applicability of the catalyst was also evaluated for the synthesis of an anti-HIV agent drug molecule. Greener, cheaper & eco-friendly GCM catalyst as well as catalytic process for synthesis of alpha-Keto Amides.